Current and desired organizational culture of the financial system of the province of Huancayo, Peru - Espinoza Yangali, Jovany Pompilio (2020)
The objective of this investigation was to identify the current organizational culture of the financial system of the province of Huancayo and the culture that they wanted, to serve as a complement to the traditional indicators of the sector. The Organizational Cul- ture Assessment Instrument (OCAI) was practiced on 412 workers from 16 financial in- stitutions. It is a quantitative, non-experimental and descriptive study.